Pengaruh Pelatihan Dan Motivasi Berwirausaha Terhadap Minat Dan Potensi Narapidana Di Lembaga Pemasyarakatan - Ananda Septiana Lestari; Muhamad Juani; Herry Fernandes Butar (Universitas Hamzanwadi, 2021)
The increase in criminal activities that occur in the community will cause an increase in Institutional Institutions (LAPAS) that will increase. The government as a policymaker in this case plans the development of prison inmates so that prisoners do not commit crimes again and have work motivation. This study aims to analyze the effect of entrepreneurship training and work motivation on entrepreneurial interest in prison inmates. The method used in this research is the Expos facto method with quantitative estimation. The population in this study were all prisoners who had attended entrepreneurship training. The data collection technique in this research is the study of literature. Data collection tools used in this study were sourced from books, journals and literature studies. The results of this study reflect what is meant by significant entrepreneurship training and motivation towards the interest of convict entrepreneurs. This means that the better entrepreneurship training and work motivation held by prison staff, the entrepreneurial interest will increase, and vice versa